Sublethal Effects of Triflumezopyrim on Biological Traits and Detoxification Enzyme Activities in the Small Brown Planthopper Laodelphax striatellus (Hemiptera: Delphacidae) - Zhang, Shuirong; Wang, Xuegui; Gu, Fuchuan; Gong, Changwei; Chen, Lin; Zhang, Yuming; Hasnain, Ali; Shen, Litao; Jiang, Chunxian (Frontiers in Physiology, 2020)
The small brown planthopper [Laodelphax striatellus (Fallén) (Hemiptera, Delphacidae)] is one of the most destructive insect pests of rice and has developed strong resistance to several kinds of chemical insecticides. Triflumezopyrim, a novel mesoionic insecticide developed by Corteva Agriscience (formerly DuPont Crop Protection), has efficient biological activity in controlling sucking insects, such as the planthopper. However, the effects of triflumezopyrim on the growth and reproduction of L. striatellus have not been reported. In this study, an F5 generation was obtained by conducting five rounds of insecticide screening on a sensitive L. striatellus strain (F0 generation). An age-stage life table procedure was used to evaluate the effects of a sublethal concentration (LC50) of triflumezopyrim on the biological parameters of L. striatellus. Compared with those of the F0 generation, the intrinsic rate of increase (r), the finite rate (λ), and the net reproductive rate (R0) of the F5 generation were significantly decreased; nevertheless, the average duration of life (T) was not significantly affected. The results of detoxification enzyme activity assays indicated that the glutathione S-transferase and cytochrome P450 monooxygenase (P450) activities in the F5 generation were significantly higher than those in the F0 generation. The contents of vitellogenin (Vg) and vitellogenin receptor (VgR) were also detected, and the results indicated that the contents of Vg and VgR in the F5 generation were significantly decreased compared to those in the F0 generation. Furthermore, we detected the relative expression of ecdysone receptor (EcR), Vg, and VgR in the F0 and F5 generations and found that the relative expression levels of Vg and VgR in the F5 generation female adults were obviously lower than those in the F0 generation (P < 0.05), whereas the relative expression of EcR was slightly increased, although the difference was not significant (P > 0.05). Based on these results, a sublethal concentration (median lethal concentration, LC50) of triflumezopyrim may inhibit the generational growth and reproduction of L. striatellus. Moreover, our results may provide a reference for further studies of the suitability and resistance mechanisms of L. striatellus subjected to a sublethal dose of triflumezopyrim.